Studies on Selective Metalation and Cross-Coupling Reactions of Oxazoles - Wagner, Raphael; Wollnitzke, Philipp; Essig, Sebastian; Gölz, Jan P.; Menche, Dirk (Synthesis, 2023)
A general study on selective functionalization of unsubstituted oxazole is reported. Specific halogenation at C2 and C5 was enabled by a sequential deprotonation strategy that was based on the different pKa values of these positions, while a halide at C4 may be introduced by an optimized halogen dance reaction. Efficient protocols for subsequent sp2–sp2 and sp2–sp3 cross-coupling reactions of the derived oxazolyl halides were then established. This modular approach was applied in the total synthesis of ajudazol A and a selected analogue, demonstrating the general feasibility of these conditions in a complex setting.
Keywords: oxazole; halogen dance reaction; halogenation; Negishi/ Suzuki cross-coupling; ajudazol A